First record and extended distribution of Otothyropsis piribebuy (Loricariidae: Hypoptopomatinae) in Brazil - Hocama, Guilherme Seiji; Martins, Fernanda de Oliveira; Severo-Neto, Francisco (Papéis Avulsos de Zoologia, 2020)
Cascudinhos are a group of small benthic fishes included in the Hypoptopomatinae subfamily, inhabiting small to moderate streams and rivers within the Neotropical region, from Venezuela to Northern Argentina. Until now, Otothyropsis piribebuy originally described from the rio Paraguay basin, in Paraguay, is the only species of the genus not recorded in Brazil. Recent samples in the rio Tererê, rio Paraguay basin, Brazil, revealed a population of Otothyropsis with uncertain taxonomic identity. Therefore, the study aimed to unveil the distribution of Otothyropsis within Brazilian territory. External morphology, osteology, measurements, and counts (plates, teeth, and rays) of these specimens from rio Tererê were compared to data from the original description of O. piribebuy, and also with specimens of O. piribebuy sampled in Paraguayan territory. Observations indicated no differences among the analyzed specimens. Furthermore, a Principal Component Analysis (PCA), carried out using log-transformed measures from Brazilian and Paraguayan specimens, showed no separation of these populations, also indicating that all analyzed specimens pertain to the same species. Based on this, a prediction map of distribution, using Maximum Entropy, was produced. The correct identification of spatial range of occurrence is an essential step to ensure the conservation of species, and the extended distribution of Otothyropsis piribebuy was confirmed, enhancing the list of neotropical fish from Brazil.